Paclitaxel Induced MDS and AML: A Case Report and Literature Review - Udit Bhaskar Bhatnagar; Daulath Singh; Alexy Glazyrin; Jill Moormeier (Case Reports in Oncological Medicine)
Therapy related acute myelogenous leukemia (AML) and myelodysplastic syndromes (MDS) have been classically linked to alkylating agents and topoisomerase inhibitors. They constitute about 1% of all AMLs. There is less evidence on association of taxanes (paclitaxel and docetaxel) with these myeloid neoplasms. We present a case of paclitaxel therapy related acute myelogenous leukemia after treatment of endometrial cancer with a regimen containing paclitaxel and carboplatin. A 63-year-old female underwent surgery followed by a total of 6 cycles of chemotherapy with carboplatin and paclitaxel. Six months after last cycle of chemotherapy, she was diagnosed with myelodysplastic syndrome with refractory anemia and excess blasts. Six weeks later, she had worsening anemia and thrombocytopenia which prompted a bone marrow biopsy which revealed acute myelomonocytic leukemia. A thorough literature review revealed 12 other case reports where taxanes have been implicated in the development of therapy related myeloid neoplasm. Based on the timeline of events in our patient, paclitaxel is the likely culprit in the pathogenesis of this myeloid neoplasm. This rare but significantly grave adverse effect should be kept in consideration when deciding on treatment options for gynecological malignancies.